2020
DOI: 10.1186/s13765-020-00534-w
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of daily intake of lycopene, antioxidant contents and activities from tomatoes, watermelons, and their processed products in Korea

Abstract: Tomatoes, watermelons, and processed tomato products contain abundant antioxidant compounds, including lycopene. In spite of the interest in the role of lycopene, little is known about the contribution of tomatoes and tomato products commonly consumed in Korea to the intake of lycopene. In this study, the daily per capita intake values of lycopene and antioxidant compounds and activities of tomatoes, watermelons, and their processed products in Korea were estimated. The daily per capita intake values of lycope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…According to a study by Yang and Shin, the TFC of edible roses ranged between 0.79 to 5.32 g/kg FM; our analysed cultivar is in this range [ 1 ]. The flowers reached significantly higher TFC values than some vegetables and fruit, such as tomatoes (0.133 to 0.474 g RE/kg FM) [ 60 ], watermelons (0.09 to 0.27 g RE/kg FM) [ 61 ], or fruit studied by Mirzaei et al, such as blackberry and black grape, whose TFC values ranged from 0.05 to 1.03 g RE/kg FM [ 62 ]. According to studies on 12 cultivars of EFs, the yellow blossoms had a higher content of flavonoids and suggested that they have a stronger antioxidant potential than other colours [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to a study by Yang and Shin, the TFC of edible roses ranged between 0.79 to 5.32 g/kg FM; our analysed cultivar is in this range [ 1 ]. The flowers reached significantly higher TFC values than some vegetables and fruit, such as tomatoes (0.133 to 0.474 g RE/kg FM) [ 60 ], watermelons (0.09 to 0.27 g RE/kg FM) [ 61 ], or fruit studied by Mirzaei et al, such as blackberry and black grape, whose TFC values ranged from 0.05 to 1.03 g RE/kg FM [ 62 ]. According to studies on 12 cultivars of EFs, the yellow blossoms had a higher content of flavonoids and suggested that they have a stronger antioxidant potential than other colours [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, attention has been focused on carotenoids that serve as vitamin A provitamins in human body, primarily on αand β-carotene and their effects on human health. Over time it was demonstrated that lycopene is a key phytochemical compound with highly beneficial effects on human health, mainly due to its antioxidant effect [5]. The first studies of the biological activity of lycopene were performed in 1959, when reduced mortality was found in laboratory mice after lycopene injection [23].…”
Section: Lycopene Contentmentioning
confidence: 99%
“…Among carotenoids, attention has been paid mainly to αand β-carotene due to their provitamin properties, but lycopene has proven over time to be a key phytochemical for its significant effects on human health. In watermelons, the lycopene content represents approximately 70-90% of all carotenoids and acts as an important phytochemical compound [5]. The main sources of lycopene in human diet are mainly tomatoes and tomato products, pink guava, and pink grapefruit.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the great interest on the part of researchers, data on the processing impact on nutritional quality are still incipient with controversial results found in the literature. Most of these studies focus on the investigation of bioactive compounds in products derived from tomatoes, such as the composition of phenolic and total flavonoid contents of tomato paste (Katırcı et al., 2020), tomato ketchup, tomato juice (Park et al., 2020), and others products, but without elaborating on these correlations (Szabo et al, 2019). Along the same line, Tan et al (2020) studied the freeze‐drying and oven‐drying effects on appearance, chemical components, and antioxidant activities of three cultivars of tomatoes and noticed a significant decrease in the 2,2‐diphenyl‐1‐picrylhydrazyl (DPPH) and ABTS radical scavenging activities when compared to fresh tomatoes.…”
Section: Introductionmentioning
confidence: 99%
“…Within the group of carotenoids, it is known that some are precursors of vitamin A such as β ‐carotene that is the most active carotenoid provitamin A, and is associated with protection against heart disease and cancer (Carvalho et al., 2006). Lycopene is another carotenoid found in high concentration in ripe tomatoes (80%) (Park et al., 2020) and their derived products, having an important antioxidant function (Matioli & Rodriguez‐Amaya, 2003). In addition, the presence of lycopene in the diet is related to reducing certain types of cancers and reducing the risk of heart attack (Carvalho et al., 2006).…”
Section: Introductionmentioning
confidence: 99%